Analysis of the children's prosocial behavior - Jin, Yongxian; Di, Yi (IJRDO - Journal of Social Science and Humanities Research, 2017)
Prosocial behaviors refer to those behaviors that meet the social expectations and requirements in peoples' social life, and that are certainly beneficial to other individuals, social groups and even the whole society. Researchers have made many achievements in the research fields of prosocial behaviors, especially involvingchildren. This paper shows teachers how to resolve the conflict between children and to analyze the children's prosocial behavior. Finally, the analysis on children's prosocial behavior is summarized.